INTEGRASI NILAI SPIRITUAL, INTELEKTUAL DAN MORAL DALAM KONSEP PENDIDIKAN SAID NURSI - Muhammad Faiz (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2013)
Bediuzzaman Said Nursi (1877-1960) was an Islamic revivalist who lived in the last period of the Ottoman caliphate in Turkey. He emerged with his book "Risale-i Nur" trying to save the faith of Muslims by revealing the miracle of Qur'an. The primarly purpose of the Risale-i Nur is the revitalization of the faith of the ordinary believers, along with moral renewal. The methodology employed in this paper is qualitative. The main corpus used is Nursi’s book of Risale-i Nur. The findings of this article reveal that the concept of education according to Said Nursi’s view is an integration of three main elements which combine religious sciences (alulum al-diniyyah) with modern cosmic science (al-ulum al-kauniyyah alhaditsah) and the values of sufism doctrine. Nursi stated that religious knowledge was the light for heart while modern science was the light of the mind. The combination of both will guide to the truth and minimize bigotry. The main curriculum of learning should study the main topics contained in the Risale-i Nur. This concept combines three holistic aspects: spirituality which come from religious schools (medrese), intelectuality which come from the scientific schools (mekteb) and morality that come from the sufistic schools (tekke).